2022
DOI: 10.1007/s42773-022-00186-7
|View full text |Cite
|
Sign up to set email alerts
|

Biochar granulation reduces substrate erosion on green roofs

Abstract: Green roofs are exposed to high winds and harsh environmental conditions that can degrade vegetation and erode substrate material, with negative consequences to ecosystem services. Biochar has been promoted as an effective substrate additive to enhance plant performance, but unprocessed biochars are susceptible to wind and water erosion. Applications of granulated biochars or chemical dust suppressants are suggested as a means to mitigate biochar and substrate erosion; however, research on biochar type and che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…Substrate water retention capacity (WRC) (ln RR = 0.211 ± 0.043, p < 0.001) and plant available water (PAW) (ln RR = 0.288 ± 0.064, p < 0.001) increased with biochar amendment by 23 and 33%, respectively (Figure 2a). Consistent patterns were also reported in the qualitative summary, with Liao et al 44 also revealing that biochar reduced substrate erosion loss (Table 1). 45−79 Biochar showed no mean effect on substrate saturated hydraulic conductivity (ln RR = −0.285 ± 0.505), total porosity (ln RR = −0.079 ± 0.104), or air-filled porosity (ln RR = −0.015 ± 0.067).…”
Section: ■ Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Substrate water retention capacity (WRC) (ln RR = 0.211 ± 0.043, p < 0.001) and plant available water (PAW) (ln RR = 0.288 ± 0.064, p < 0.001) increased with biochar amendment by 23 and 33%, respectively (Figure 2a). Consistent patterns were also reported in the qualitative summary, with Liao et al 44 also revealing that biochar reduced substrate erosion loss (Table 1). 45−79 Biochar showed no mean effect on substrate saturated hydraulic conductivity (ln RR = −0.285 ± 0.505), total porosity (ln RR = −0.079 ± 0.104), or air-filled porosity (ln RR = −0.015 ± 0.067).…”
Section: ■ Resultssupporting
confidence: 84%
“…The highly variable effects of biochar on saturated hydraulic conductivity (Figure a) are likely associated with a large variation of GI substrate composition and texture. Although biochar erosion loss is a concern on green roofs, a recent study showed a reduction of total substrate erosion losses from biochar-amended green roofs due to increased moisture retention and vegetation cover . Losses of biochar particles in discharge water are also a concern; in the meta-analysis, we found a variable but increasing trend of TSS concentrations in discharge with biochar application (Figure b), likely due to fragmentation of friable biochars …”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…As compared to fine particles, larger particles are more resistant to biochar loss caused by wind and water [59]. Medium to large biochar particles or heavy biochar (processed biochar) were suggested to be used to limit the biochar loss [60,65,76].…”
Section: Biochar Variables: Application Method Amendment Rate and Par...mentioning
confidence: 99%
“…In addition, a shadowing effect may appear in the photocatalytic reaction of a wood biochar-based photocatalyst [159,160]. This phenomenon is usually due to the fact that the light cannot fully penetrate the thick or dense part of the photocatalyst, thus reducing the effective light absorption on the surface of the catalyst, resulting in some areas not being irradiated by light and affecting the catalytic reaction [161][162][163]. The shadowing effect can be reduced by the following strategies: (1) Adjusting the structure of the catalyst [164]: by designing the catalyst structure with a larger pore size and lower density, the penetration depth of light can be increased and the shadowing effect can be reduced.…”
Section: Limitation Of Woody Biochar-based Photocatalysts In Water Tr...mentioning
confidence: 99%